Mothers’ Opisthorchis viverrini infection status and raw fish dish consumption in Lao People’s Democratic Republic: determinants of child infection status - Araki, Hitomi (Trop Med Health, 2018)
BACKGROUND: Opisthorchis viverrini (Ov) infection is one of the foodborne trematodiases, which is highly endemic in Lao People’s Democratic Republic (PDR). The infection occurs especially when people eat raw fish containing Ov metacercariae. As eating raw fish is a traditional culture in Lao PDR, changing this behavior is difficult. A new approach is necessary to control Ov infection because people easily get re-infected even after taking praziquantel unless they change their behaviors. This study aimed to explore factors associated with Ov infection among children and to identify the existing behaviors and perception that might contribute to the control of Ov infection in Lao PDR. We conducted a cross-sectional study in Yommalath district, Khammouane province, in Lao PDR in August and September 2015. In this cross-sectional study, we used a semi-structured questionnaire and interviewed 348 mothers who had a child aged 5–15 years. We also collected the fecal samples from each mother-child pair and used the Kato-Katz method (three slides/sample) to detect Ov eggs. RESULTS: Of 284 children, 82.8% were infected with Ov. The children were more likely to be infected with Ov when their mothers were infected with Ov (adjusted odds ratio [AOR] 10.45, 95% confidence interval [CI] 3.13–34.86) or when their mothers liked raw fish dishes (AOR 2.47, 95% CI 1.07–5.69). Even though most mothers are primarily in charge of cooking family meals, fathers were also involved in the preparation of raw fish dishes. CONCLUSION: This study suggests that a new approach to control Ov infection should target families or communities, rather than children only. Cooking or food preparation behaviors should be investigated in more depth.